Selected decisions and selected documents of the International Monetary Fund : sixteenth issue, Washington, DC, May 31, 1991 - International Monetary Fund (Washington, D.C., 1991)
This volume is the Sixteenth issue of Selected decisions and selected documents of the International Monetary Fund. It contains the decisions, interpretations, and resolutions of the Executive Board and the Board of Governors.
usc 07/09/2021
Ref.
Keywords: International Monetary Fund